High-energy x-ray Talbot–Lau radiography of a human knee. (1st August 2017) - Horn, F; Gelse, K; Jabari, S; Hauke, C; Kaeppler, S; Ludwig, V; Meyer, P; Michel, T; Mohr, J; Pelzer, G; Rieger, J; Riess, C; et al.
Abstract: We report on a radiographic measurement of an ex vivo human knee using a grating-based phase-contrast imaging setup and a medical x-ray tube at a tube voltage of 70 kV. The measurement has been carried out using a Talbot–Lau setup that is suitable to achieve a high visibility in the energy regime of medical imaging. In a medical reading by an experienced trauma surgeon signatures of chondrocalcinosis in the medial meniscus have been identified more evidently using the dark-field image in comparison to the conventional attenuation image. The analysis has been carried out at various dose levels down to 0.14 mGy measured as air kerma, which is a dose comparable to clinically used radiographic devices. The diagnosis has been confirmed by a histological analysis of the meniscus tissue. In the introduced high-frequency filtered phase-contrast image the anterior and posterior horn of the medial meniscus and the posterior cruciate ligament have also been visible. Furthermore, atherosclerotic plaque is visible in both imaging modalities, attenuation and dark-field, despite the presence of overlaying bone. This measurement, for the first time, proves the feasibility of Talbot–Lau x-ray imaging at high-energy spectra above 40 kVp and reasonable dose levels with regard to spacious and dense objects.